Cochlear implantation surgery in patients with narrow facial recess. (September 2013) - Wang, Line; Yang, Jigang; Jiang, Changcan; Zhang, Daoxing
Abstract Conclusion: The new method of facial recess enlargement through suspending, antedisplacing, and adhering the chorda tympani nerve to the posterior wall of the auditory canal can expose the round window, make electrode insertion easier, and preserve the function of the facial nerve and chorda tympani nerve. Objective: To describe and report cochlear implantation surgery in patients with narrow facial recess, including surgical technique and postoperative outcomes. Methods: Cochlear implantation surgery was performed in our hospital in 39 cases with narrow facial recess by enlarging the facial recess. To enlarge the distance between the facial nerve and chorda tympani nerve, the chorda tympani nerve was suspended. The chorda tympani was anteplaced and adhered to the posterior wall of the auditory canal. Results: Among the 39 cases, the narrowest distance between the facial nerve and the chorda tympani nerve was less than 1.0 mm. All patients successfully underwent cochlear implantation surgery. No injuries of the facial nerve, chorda tympani nerve, or the posterior wall of the auditory canal were reported in any of the patients. There were significant differences in the injuries of the facial nerve, chorda tympani nerve, and posterior wall of the auditory canal in these cases compared with previous approaches to this operation.